AVAILABILITY AND COST-BENEFIT OF USING COCONUT RESIDUES AS BIOMASS ENERGY SOURCE IN TOP COCONUT-PRODUCING MUNICIPALITIES IN NEGROS OCCIDENTAL, PHILIPPINES - Montaño, Melanie Roma; Silapan, Judith R.; Orillo, Yuleta R.; Nazareno, Patricia Ann G. (Journal of Agriculture and Technology Management; Journal of Agriculture and Technology Management (JATM) Volume 19 Issue 1, January-June 2016, 2016)
Coconut residues as a potential energy feedstock are well-documented. However, studies dealing with its availability and cost-benefit effect on the environment and the economic situation of coconut farmers in the Philippines are limited. This study answered these concerns through theoretical and available biomass estimation, greenhouse gas (GHG) estimation, farmers’ willingness to supply (WTS) determination and additional income estimation from selling residues as biomass feedstock in Negros Occidental, Philippines. A total of seven municipalities was surveyed. Descriptive statistics was used to analyze data. The total available potential of coconut biomass in the surveyed municipalities was 76,148.18 MJ/ha/yr. Computations revealed that fully converting the province’s coconut biomass available potential to electricity will generate 392.33x10 6 kg of CO 2 , which is half of what is produced when using pulverized coal. Further computations showed revenue losses for the farmers ranging from Php 698.59 - 1,284.12/yr. Use of all available coconut residues can generate ample energy and GHG emissions lower than the traditional fuel. However, it does not contribute to the economic upliftment of coconut farmers. The current market price for biomass feedstocks is too low to be an alternative source of income to traditional coconut residue use.